Animals: Mythology And Worship (Journal of Namibian Studies : History Politics Culture, 2023)
Ancient Indians had recognized the animals right to co-exist with man and therefore they were loved, nurtured and even worshipped. In order to impress upon the commoners about their importance, the animals were given the status of gods and goddesses. Mostly in the ancient Indian literature, animals are depicted as ‘vahanas’ or vehicles of the gods. Airavata; vahana of lord Indra is one of the very popular examples of it. Airavata means “the one who knits or binds the clouds”. The Upanishads contain detailed descriptions about horses and cattle. The Garudapurana contains life-histories of fishes and turtles. Although there are no special books which dedicated to a special animal (besides Matsaya Purana, the name looks like that it is about fishes but it is about the stories of lord Vishnu), Nagamahdimya, Nandi-purdoa, Mayiratrahimya and Pashu-puriltia are some good accounts about them.